Tuneable helices of plasmonic nanoparticles using liquid crystal templates: molecular dynamics investigation of an unusual odd–even effect in liquid crystalline dimers. Issue 53 (27th May 2022) - Pawlak, Mateusz; Bagiński, Maciej; Llombart, Pablo; Beutel, Dominik; González-Rubio, Guillermo; Górecka, Ewa; Rockstuhl, Carsten; Mieczkowski, Józef; Pociecha, Damian; Lewandowski, Wiktor
Abstract : Liquid crystalline (LC) dimers formed helical nanofilaments depending on the parity of the alkyl linker, revealing an unusual odd–even effect. Doping LC with Au nanoparticles evidenced that helical pitch was regulated by the length of the linker. Abstract : Liquid crystalline (LC) dimers formed helical nanofilaments depending on the parity of the alkyl linker, revealing an unusual odd–even effect. Molecular dynamics simulations were used to investigate the observed tendency. Elongation of the linker translates to an increase of the pitch of the helices, which allows achieving tuneable helical assemblies of Au nanoparticles doped to the LC matrix. The impact of the tuneable pitch of helices on the chiral optical properties of composites was investigated with full-wave simulations based on the T-matrix method.